English Fun Reading Program: Improving Children's Motivation and Proficiency in English Reading at Rumah Belajar Al Ilmi Podorejo, Pringsewu - Dian Rakhmawati; Yuniarti, Fatma (Universitas Kristen Cipta Wacana, 2025)
This study explores the implementation and effectiveness of the English Fun Reading Program in improving childrens learners’ reading motivation and English proficiency at Rumah Belajar Al Ilmi, an informal community learning center in Pringsewu, Lampung, Indonesia. Designed for children aged 5 to 9, the program integrated storytelling, phonics-based games, read-aloud sessions, and culturally relevant materials within an interactive learning environment. Employing a qualitative descriptive approach and guided by Participatory Action Research (PAR), the study was conducted over multiple intervention cycles that included planning, action, observation, reflection, and replanning. Data were collected through field observations, video documentation, informal interviews, and reflective journals, and analyzed using thematic analysis. Findings revealed significant improvements in students' phonemic awareness, vocabulary acquisition, sentence reading ability, and enthusiasm toward English reading activities. The number of children able to recognize letters, read simple sentences, and participate actively in group reading sessions increased substantially. Additionally, learner motivation and engagement rose consistently throughout the program. These outcomes support key educational theories, including Vygotsky’s Zone of Proximal Development, Krashen’s Comprehensible Input Hypothesis, and phonemic awareness frameworks by Ehri. The study concludes that participatory, culturally responsive, and enjoyable literacy interventions can serve as powerful tools for enhancing early English literacy in under-resourced educational settings.